Rule-based lip-syncing algorithm for virtual character in voice chatbot - Felicia Priscilla Lovely; Arya Wicaksana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Virtual characters changed the way we interact with computers. The underlying key for a believable virtual character is accurate synchronization between the visual (lip movements) and the audio (speech) in real-time. This work develops a 3D model for the virtual character and implements the rule-based lip-syncing algorithm for the virtual character's lip movements. We use the Jacob voice chatbot as the platform for the design and implementation of the virtual character. Thus, audio-driven articulation and manual mapping methods are considered suitable for real-time applications such as Jacob. We evaluate the proposed virtual character using hedonic motivation system adoption model (HMSAM) with 70 users. The HMSAM results for the behavioral intention to use is 91.74%, and the immersion is 72.95%. The average score for all aspects of the HMSAM is 85.50%. The rule-based lip-syncing algorithm accurately synchronizes the lip movements with the Jacob voice chatbot's speech in real-time.